EVALUASI KELONGSORAN PADA RUAS JALAN WELERI – SUKOREJO KM. 55 KAB. KENDAL - Galieh Alfanto; Yusni Apriatmoko; Indrastono Dwi Atmanto; Bambang Pardoyo (Jurnal Karya Teknik Sipil, 2013)
This undergraduate thesis is about the stability of slopes on Weleri roads, mechanisms and mitigation in Weleri – Sukorejo roads, Kendal Regency. The road was built to support economic growth in Weleri and its surroundings. The road across the hills and valleys that contain clay shale. Catastrophic landslide and slope occurs in Weleri – Sukorejo roads Km. 55, Kendal Regency. This undergraduate thesis involves conditions which the motions of the soil on the slope because of slope unstability, manual calculation slope stability with Fellinius methods and Simplified Bishop methods, geotechnical analysis and the use of retaining wall with bored pile reinforcement as an alternative method of reinforcement. Geotechnical analysis using Plaxis finite element software. Plastic and elastic model of Mohr-Coulomb failure criterion was chosen as a model soil. Analysis showed that the most optimum avalanche  mitigation is to install a retaining wall combine with group of bored pile reinforcement with a diameter of 1 meter which is modeled with elastic-plastic beam elements. By using retaining wall combine with geoup of bored pile reinforcement, minimum slope safety factor beincreased and reached 1.562.